KEDUDUKAN HADIST QUDSI SEBAGAI SUMBER HUKUM ISLAM - HILAL SOLIKIN (STIT DARUL ULUM KOTABARU, 2022)
Hadith is everything that is quoted from the Prophet Muhammad SAW in the form of words, deeds and taqrir or other than that. Hadith is a source of Islamic Shari'a law because of its position as God's revelation conveyed by the Prophet Muhammad SAW. As one form of hadith, hadith Qudsi is a hadith that in a sentence has a noble position because it relies directly on Allah SWT. This reliance is what makes this hadith Qudsi or Divine or Rabbani, which means that everything returns to Allah SWT. The transmission of this hadith is done through direct revelation or through inspiration and dreams. This is what distinguishes the Hadith Qudsi from the Qur'an which is absolutely conveyed through revelation. The position of the Qudsi hadith as a source of Islamic law remains like the other hadiths, namely the second source of law after the Qur'an as the first source of law. It is not because of its qudsi wording that it aligns with the Qur'an, but the Qudsi hadith still has the same position as the other hadiths, namely bayan lil al-Qur'an, which explains the verses of the Qur'an both explicitly and implicitly so that the legal content stored in it can be conveyed clearly.